(untitled) (Iraqi Journal of Civil Engineering, 2024)
In this paper, a practical method of analysis of the pile displacements is proposed on the basis of the theory of load-transfer curves widely used in pile design and analysis. The parameters of the load-transfer curves for piles under axial load (called t-z, q-z curves) or lateral load (called P-Y curves) were correlated with the number of blows Nspt measured during the standard penetration test (SPT). Well documented case histories of full-scale axial or lateral loading tests on single piles in sand were collected, and the analysis of the experimental results led to define the parameters of the load-transfer curves. Two practical methods of computation of a single pile under an axial load or a lateral load were proposed to be used within the scope of a pile foundation project. At last, a validation process of the load-transfer curves was undertaken by direct comparison of the predicted pile displacements to those measured during other pile loading tests, which showed a good predictive capability of the two proposed methods